The principle of the primacy of the resolution of the merits and the new Code of Civil Procedure (Revista do Tribunal Regional Federal da 3ª Região, 2016)
The presentation of some rules for applying the principle of the primacy of the resolution of the merits had a single objective: to show that it is necessary to treat the Brazilian civil process of the 21st century as an efficient mechanism for producing constitutionally legitimate results. The judge of the 21st century must be seen as a guarantor of fundamental rights, and among these is undoubtedly the fundamental right of access to justice, understood here as the fundamental right to the production of constitutionally legitimate results through the process. Applying this principle will certainly require a change in the attitude (and culture) of judges: they need to see themselves as members of a working community, through which, together with the parties (and their lawyers), they will build the right decision for the specific case. This working community must therefore be understood in line with the paradigm of the Democratic State of Law, established by Article 1 of the Constitution of the Republic. The Brazilian civil procedure of the Democratic State, which the CPC of 2015 consolidates on the basis of a model established by the Constitution of the Republic of 1988, must be a participatory, cooperative process, capable - for this very reason - of leading to constitutionally legitimate decisions, which will preferably be decisions on the merits.
Keywords: New Code of Civil Procedure; Principle of primacy of resolution of the merits; application